Hyastenus verreauxii A. Milne-Edwards, 1872, a synonym of Hyastenus elatus Griffin & Tranter, 1986: lectotype designation and reversal of precedence (Crustacea: Brachyura: Majoidea: Epialtidae) - Lee, Bee Yan; Ahyong, Shane T.; Low, Martyn E. Y.; Ng, Peter K. L. (Zootaxa, 2018)
The majoid spider crab, Hyastenus verreauxii A. Milne-Edwards, 1872 (family Epialtidae), was described based on the material from “Nouvelle-Hollande” (= Australia) in the “Collection du Muséum”, that is, the Muséum national d’Histoire naturelle, Paris (MNHN). It was noted by A. Milne-Edwards (1872: 250) that the species is morphologically similar to H. diacanthus (De Haan, 1839) but differs in having a less developed hepatic region, as well as longer and straighter pseudorostral spines. Miers (1879: 26) synonymised H. verreauxii under H. diacanthus with no detailed explanation, and Miers (1886: 56) noted that this species “is probably a variety of Hyastenus diacanthus”. Haswell (1880: 442; 1882: 20) identified Australian specimens as H. diacanthus and listed H. verreauxii as its junior synonym. Ortmann (1893: 55) followed the consensus but regarded H. verreauxii as a subspecific taxon (“var.”) of H. diacanthus. Serène & Lohavanijaya (1973: 53) treated H. verreauxii as a synonym of H. diacanthus. However, none of these authors provided a detailed explanation for the decision to synonymise this species nor was the type examined. This species has not been treated by subsequent workers.